PET hydrolysing enzymes catalyse bioplastics precursor synthesis under aqueous conditions. Issue 14 (24th June 2019) - Parisi, Daniele; Riley, Christopher; Srivastava, Abhishek S.; McCue, Hannah V.; Johnson, James R.; Carnell, Andrew J.
Abstract : Poly(ethylene terephthalate) hydrolase (PETase) was used to catalyse a double transesterification to convert FDCA dimethyl ester to the bioplastics precursor bis-butandiol ester in good yield under aqueous conditions. Abstract : Poly(ethylene terephthalate) hydrolase (PETase) was used to catalyse a double transesterification to convert FDCA dimethyl ester to the bioplastics precursor bis-butandiol ester in good yield under aqueous conditions. The presence of high water content was important for high transesterification selectivity. CAL-A and CAL-B lipases showed low activity or extensive hydrolysis. The PETase bioconversion was demonstrated at gram scale and the transesterification products can be selectively extracted for use in polymerisation reactions.